2021
DOI: 10.3390/cancers13235993
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic Mechanisms and Therapeutic Targets in Chemoresistant High-Grade Serous Ovarian Cancer

Abstract: High-grade serous ovarian cancer (HGSOC) is the most common ovarian cancer subtype, and the overall survival rate has not improved in the last three decades. Currently, most patients develop recurrent disease within 3 years and succumb to the disease within 5 years. This is an important area of research, as the major obstacle to the treatment of HGSOC is the development of resistance to platinum chemotherapy. The cause of chemoresistance is still largely unknown and may be due to epigenetics modifications that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 112 publications
(153 reference statements)
0
17
0
Order By: Relevance
“…DNA methylation mediates the silencing of transcription and aberrant gene promoter methylation. The role of DNA methylation in the progression and chemoresistance in high-grade serous ovarian cancer at both the genome-wide and individual gene level has been recently reviewed [ 75 ].…”
Section: Folate Homeostasis Folate Transport and One-carbon Metabolismmentioning
confidence: 99%
“…DNA methylation mediates the silencing of transcription and aberrant gene promoter methylation. The role of DNA methylation in the progression and chemoresistance in high-grade serous ovarian cancer at both the genome-wide and individual gene level has been recently reviewed [ 75 ].…”
Section: Folate Homeostasis Folate Transport and One-carbon Metabolismmentioning
confidence: 99%
“…The overall survival rate of HGSOC has not been improved in the last three decades, and most patients develop recurrent disease within 3 years and died from the disease within 5 years. HGSOC is extremely regulated by epigenetic modifications ( 27 ). M 6 A plays an important role in numerous biological processes, which contributes to cancer development, cancer cell proliferation and cancer stem cell self-renewal ( 28 , 29 ).…”
Section: Discussionmentioning
confidence: 99%
“…Macintyre et al [53] identified seven copy number signatures that were stable between diagnosis and disease relapse, indicating that copy number signatures at diagnosis may predict overall survival and platinum resistance [54] . Different mutational processes generate unique combinations of mutation types, termed mutational signatures [55] . The Catalogue of Somatic Mutations in Cancer (COSMIC) has revealed many mutational signatures across the spectrum of human cancer types.…”
Section: Geneticsmentioning
confidence: 99%
“…The Catalogue of Somatic Mutations in Cancer (COSMIC) has revealed many mutational signatures across the spectrum of human cancer types. Analysis of COSMIC mutational signatures in ovarian cancer reveals a prevalence of signature 1B [ 56 ] .…”
Section: Future Directionsmentioning
confidence: 99%